MATERIAL PROCESS IN THE ENGLISH CLAUSE: FUNCTIONAL GRAMMAR APPROACH - Eva Tuckyta Sari Sujatna (Universitas Padjadjaran, 2009)
This research is entitled Material Process in English Clause: A Functional Grammar Approach. This research discusses three main points: (1) the verbs can be categorized into material process; (2) the participants involve in the material process; and (3) the clause patterns of material process. This research employs a Functional Grammar Approach (FGA). This research method used is descriptive method, which employs paraphrases and reference techniques. The result of this research shows that (1) the verbs: run, kill, make, destroy, give, sing, play, break, go, snore, sleep, buy, bit, put, paint, and consider can be categorized into the verbs of material process; (2) the participants involve in the material process can be agent, affected, effected, recipient, beneficiary, range, and instrument; and (3) the clause patterns of material process can be intransitive, monotransitive, ditransitive, and complex transitive.